Implementation of the Make a Match Cooperative Method in Learning to Analyze the Building Elements of Poetry - Marta Zakaria; Salam; Wa Ode Irawati (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study was conducted with the following objectives: to describe the implementation of the make a match cooperative learning method in teaching students in the 10th grade at Posigadan State High School to analyze the structural elements of poetry; to describe the results of implementing the make a match cooperative learning method in teaching students in the 10th grade at Posigadan State High School to analyze the structural elements of poetry; describe the obstacles in learning to analyze the structural elements of poetry after using the make a match cooperative learning method in the 10th grade at Posigadan State High School, and describe solutions to overcome the obstacles in learning to analyze the structural elements of poetry after using the make a match cooperative learning method in the 10th grade at Posigadan State High School. This study employed the Make a Match cooperative learning method. The research method used was qualitative. This study utilized a descriptive qualitative approach, specifically to describe the implementation of the Make a Match learning method in the 10th-grade class at Posigadan State High School. The data collection techniques employed included observation, interviews, documentation, and achievement tests. The results of this study indicate that the implementation of the Make a Match cooperative learning method successfully helped students understand the material on analyzing the elements of poetry. The average score obtained by the 10th-grade students at Posigadan State High School was 80, falling into the “good” category. At the same time, the implementation of the Make a Match cooperative learning method was successful because it created an active and enjoyable learning environment for both students and teachers.